Institutional Connection and Social Entrepreneurship: The Case of Father Georgi Fotakiev’s Drug Addiction Treatment Community - Nedelchev, Adrian; Dentchev, Nikolay (Research Papers, 2025)
Social entrepreneurship is an effective approach to addressing social issues through innovative solutions that generate public value. This article examines the impact of institutional support from the Bulgarian Orthodox Church on social entrepreneurship. The study focuses on a case of support exemplified by an Orthodox therapeutic community for drug addiction recovery, founded by Father Georgi Fotakiev and a group of dedicated priests. The findings reveal a unique model of institutional support, differing from approaches observed in other churches worldwide. The article presents conclusions that can contribute to building a model for sustainable support of social entrepreneurship in the face of complex social challenges.